An Integrated Physical Map for the Short Arm of Human Chromosome 5 - Peterson, Ellen T.; Sutherland, Robert; Robinson, Donna L.; Chasteen, Leslie; Gersh, Meryl; Overhauser, Joan; Deaven, Larry L.; Moyzis, Robert K.; Grady, Deborah L. (Genome Research, 1999)
The short arm of human chromosome 5 contains ∼48 Mb of DNA and comprises 1.5% of the genome. We have constructed a mega-YAC/ STS map of this region that includes 436 YACs anchored by 216 STSs. By combining and integrating our map with the 5p maps of other groups using the same recombinant DNA library, a comprehensive map was constructed that includes 552 YACs and 504 markers. The YAC map covers >94% of 5p in four YAC contigs, bridges the centromere, and includes an additional 5 Mb of 5q DNA. The average marker density is 95 kb. This integrated 5p map will serve as a resource for the continuing localization of genes on the short arm of human chromosome 5 and as a framework for both generating and aligning the DNA sequence of this region.